Gender effects on mental health symptoms and treatment in college students. Issue 1 (2nd January 2021) - Seehuus, Martin; Moeller, Robert W.; Peisch, Virginia
Abstract: Purpose: Mental health problems are a growing concern on college campuses. Although postsecondary institutions often provide mental health services to students free of charge, it is unclear which students access such treatment and why. Methods: This study examined predictors of mental health treatment among college students. 2, 280 students completed an online survey to assess demographic variables, mental health symptoms (depression, anxiety), stress and prior/current mental health treatment. Results: After accounting for symptom severity, men were less likely to receive treatment for mental health problems and LGBQ students were more likely to receive treatment. That difference was not evident at higher levels of depression and anxiety. Finally, self-reported anxiety but not depressive symptoms predicted being in mental health treatment. Conclusions: These findings can help inform efforts to target college students who could benefit from treatment but are not seeking it.